2000
DOI: 10.1046/j.1440-1681.2000.03306.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Timing Of Inspiration And Expiration Affects Respiratory Sinus Arrhythmia

Abstract: 1. The effect of a variation in inspiration and expiration times on heart rate variability was studied in 12 healthy subjects (mean age 30+/-6 years; five females). 2. Two 2 min trials of controlled breathing, with either short inspiration followed by long expiration or long inspiration followed by short expiration, were compared. Average expiration/inspiration time ratios were 1.0 and 3.4, respectively. The respiration rate in both trials was approximately 10 cycles/min. 3. In trials with short inspiration fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
3
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 26 publications
6
103
3
4
Order By: Relevance
“…Generally speaking, we know that HRV is higher when exhalations last longer than inhalations (Strauss-Blasche et al, 2000). Furthermore, in a study investigating specifically the effect of the i/e ratio when breathing at 6 breaths/min (Diest et al, 2014), participants reported more relaxation, positive energy, stress reduction, and mindfulness with a low i/e ratio (exhales > inhales), compared to a high i/e ratio (inhales > exhales).…”
Section: Resonance Frequency Breathing (Rfb)mentioning
confidence: 97%
“…Generally speaking, we know that HRV is higher when exhalations last longer than inhalations (Strauss-Blasche et al, 2000). Furthermore, in a study investigating specifically the effect of the i/e ratio when breathing at 6 breaths/min (Diest et al, 2014), participants reported more relaxation, positive energy, stress reduction, and mindfulness with a low i/e ratio (exhales > inhales), compared to a high i/e ratio (inhales > exhales).…”
Section: Resonance Frequency Breathing (Rfb)mentioning
confidence: 97%
“…It is well known [23][24][25][45][46][47][48]51,52 that the phase of respiration influences the peripheral autonomic nervous system's outflow to the heart. However, till now it has never been shown when exactly this happens inside the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Description of cardiorespiratory interaction in terms of coupling functions yields a new technique for the quantification of respiratory-related HRV. HRV is one of the central tools of psychophysiology and behavioural medicine 44 , and the respiratory component is a significant part of it [23][24][25][45][46][47][48] , representing mainly the vagal or parasympathetic part of the autonomic nervous system influences. Having introduced the time-continuous phase of the ECG, we obtain a continuous description of the HRV via the instantaneous frequency _ j e Ă°tÞ, instead of the commonly used discontinuous beat-to-beat description.…”
Section: Es Ps Eps Egmentioning
confidence: 99%
“…This is consistent with physiologic observations. Indeed, during free breathing, E/I has been measured at 1.8 (24) . For a t varying between ‐ c and 0, this equation describes a realistic breathing cycle.…”
Section: Methodsmentioning
confidence: 99%